Breast Microcalcification: Diagnostic Value of Calcified and Non‐calcified Cores on Specimen Radiographs. Issue 2 (7th January 2013) - Gümüş, Hatice; Mills, Pippa; Fish, David; Gümüş, Metehan; Devalia, Haresh; Jones, Sue E.; Sever, Ali R.
Abstract To determine if the specimen without calcification, as depicted on specimen radiography, made any contribution to the final histopathological diagnosis in comparison to the specimen with calcification. The records of 1312 stereotactic vacuum‐assisted biopsies for breast microcalcifications between February 2000 and December 2010 were reviewed retrospectively. Following specimen x‐ray the biopsy tissues with and without microcalcifications were sent in two separate pots (pot 1 and pot 2 respectively). The number of cores in each pot and the number of calcium specks within the cores were recorded. In 1135 of the 1312 (86%) cases the histopathological findings were similar for pot 1 and pot 2. In 165 cases (13%) the diagnosis was made solely on pot 1 while cores in pot 2 did not reveal any additional pathology. In 12 biopsies (1%) the significant pathology was only present in the specimen without any calcification. For "microcalcification only" breast lesions the specimen containing calcium will yield a correct diagnosis in 99% of cases. Cores containing no calcification rarely contribute to the diagnosis on their own, but in 87% of cases an accurate diagnosis would still have been made even if the targeted calcification had been missed.